Mères seules et belles-mères. Normes conjugales et maternelles en tension. - Manon Réguer-Petit (Genre, Sexualité et Société)
Based on an ethnographic field made in two associations (one of single-mothers and the other of stepmothers), and on 56 interviews carried out with members and non-members of those associations, this article seeks to interrogate how single-motherhood and step-motherhood affect maternity norms of women. It shows that those norms vary according to the women’s family trajectory. The experience of single-motherhood simultaneously leads to a demand of women independence out of the nuclear family model and to a reaffirmation of the prominent and naturalized mother-child bond. Conversely, the experience of step-parenthood leads to a criticism of the maternal identity and to a valorization of the conjugal relationship. The analysis reveals the way associations affect women’s norms while a study conducted in Ile-de-France with women who are non-members of associations reveals how social position and prior family trajectory of women affect their norms of maternity and conjugality.